7.0 T high-resolution 1H-MR spectroscopy of metabolic changes induced by chronic codeine phosphate in rat hippocampus. Issue 13 (9th September 2015) - Cao, Zhen; Lin, Pei-yin; Shen, Zhi-wei; Xiao, Ye-yu; Wu, Ren-hua
Abstract : Codeine phosphate is used widely to treat cough and pain. It is actually a sedative, but is known to cause codeine dependence. The exact mechanisms of codeine dependence are not fully understood, but are generally believed to be related to drug-induced neuroadaptation. Metabolites changes can provide information for pathological processes and mechanisms before the shape change. It is very useful for the diagnosis and treatment of drug addiction. We used 1 H NMR spectroscopy in vivo to measure the concentrations of cerebral metabolites in the hippocampus of rats subjected to repeated codeine treatment. After 2 months of codeine treatment, the concentration of N -acetylaspartate was significantly decreased in hippocampi, as was that of glutamate, choline, and taurine. Our study highlights the potential use of metabolic profiling to enhance our understanding of metabolite alteration associated with codeine dependence. Abstract : Supplemental Digital Content is available in the text.